ANALYSIS OF TRAINING AND CAREER DEVELOPMENT PROGRAMS ON EMPLOYEES OF PT GRAMEDIA ASRI MEDIA BRANCH WORLD EMERALD BINTARO TANGERANG SELATAN - Pusporini Palupi; Rita Larassati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
This study aims to determine the training held by PT Gramedia Asri Media World Emerald Bintaro, to determine career development at PT Gramedia Asri Media World Emerald Bintaro, to determine training in career development at PT Gramedia Asri Media World Emerald Bintaro. The research method used in this research is a qualitative method. The sampling technique used was non-probability sampling technique, namely purposive sampling. Data collection techniques using observation, interviews, documentation and triangulation. Data analysis techniques used data collection, data reduction, data presentation and conclusions. Based on the test results, the existing training in the company is deemed good enough and according to the standards, it's just that the training instructors feel boring and the materials used are just that because they haven't received new material from the head office. There is no career development in the company because the company uses a contract work system. Training in career development carried out by companies cannot guarantee that career development is held because the company wants to always update employees. Keywords: Training, Career Development, Employees Performances